Biofunctional properties and production of peptides from Fermented cheddar cheese whey fractions using Limosilactobacillus fermentum - Bhagyashree Das, Kunal Gawai, Kaushik Das, Hiral Kumari Patel and Subrota Hati (Indian Journal of Dairy Science, 2026)
This investigation was conducted to analyse the antioxidant activity, proteolytic activity and ability of short-chain fatty acids (SCFAs) production from fermented cheddar cheese whey fractions inoculated with Limosilactobacillus fermentum, MF951096 (M4) @ 2.5% when incubated at 37°C for 48 h. Ultrafiltration membranes with appropriate molecular weight thresholds were used to isolate low-molecular-weight peptides from fermented whey, including the 3 kDa permeate, 10 kDa permeate, and retentate fractions. In acidity and pH profile, there was no significant difference observed. Significantly higher peptide content (7.84mg/mL) and antioxidant activity (65.81%) were observed in the 10 kDa retentate fraction; however, no significant difference in lactic count was observed among the fractions. Also we characterized the peptide fractions by analysing their chromatographic peaks using RP-HPLC.  The 10 kDa retentate fraction produced the most SCFA i.e. 46.68 μg/mL acetic acid, 21.59 μg/mL propionic acid, and 5.27 μg/mL butyric acid, respectively. From this investigation, we concluded that the conversion of dairy waste into bioactive molecules presents a novel approach with conceivable applications in the dairy, food and pharmaceutical sector.